Laras bahasa: melihat ciri laras bahasa iklan dan beberapa perbezannya dengan laras bahasa lain / Rahmat Ghazali - Ghazali, Rahmat (Universiti Teknologi MARA Cawangan Pahang, 1993)
The existence of language registers within a language is an aspect which indicates a dynamic feature that qualifies it as a language of commerce, a language of law and most of all a language of knowledge. This article discusses the concept of language registers and exhibits the dominant features of commercial language register particularly the Malay language register of advertisement. To show that the language of advertisement is a register by itself, a comparison of advertisement language register to other language registers is also presented.